Improved ultraviolet stability of fullerene-based organic solar cells through light-induced enlargement and crystallization of fullerene domains - Barulina, Elena; Khodr, Anass; Dkhil, Sadok Ben; Perkhun, Pavlo; Quiroz, Yatzil Alejandra Avalos; Koganezawa, Tomoyuki; Yoshimoto, Noriyuki; Köntges, Wolfgang; Schröder, Rasmus R.; Pfannmöller, Martin; Margeat, Olivier; Ackermann, Jörg; et al. (Thin solid films, 2022)
Organic solar cells (OSCs) are a promising technology with the potential for low-cost manufacturing. However, to translate to economically viable applications, long-term stability is a fundamental requirement. Amongst intrinsic degradation pathways the sensitivity of OSC to ultraviolet (UV) light severely limits their photostability. Here, we focus on the impact of UV on the stability of solar cells based on well-known fullerene-based blends processed with 1,8-diidooctane (DIO) as additive. The post-annealed devices resulting in DIO-free blends are directly compared to as-cast devices containing residual DIO. After a pronounced initial burn-in, as-cast devices demonstrate a self-healing effect leading to stable solar cells under prolonged exposure to UV light. This initial burn-in can be considerably reduced in annealed devices with a suitable heating process, resulting in very stable solar cells under UV-containing light over a long time period. Under UV-free LED light, solar cells are stable, which implies a direct impact of UV on the performance evolution of devices. Advanced characterization techniques were used for in-depth morphological analyses under light exposure to distinguish the observed UV-related processes in the polymer blends. Our results point thus towards the presence of two processes occurring under UV-light within as-cast devices involving fullerenes, one causing a performance degradation and the other allowing a repair tending towards a performance stability. Due to an improved initial crystal order within annealed devices, the process related to the degradation is in the minority. The UV stability of devices can be attributed to the UV light-induced diffusion of fullerenes, leading jointly to the enlargement of the initial existing fullerene domains and to their crystallization under UV light. These results path the way for a better understanding of the stability of efficient normal OSCs under simulated sunlight.